Peran Brand Knowledge Memediasi Pengaruh Daya Tarik Iklan terhadap Purchase Intention: Studi pada Calon Konsumen Layanan Fotografi Darma Project di Kota Denpasar - Ni Kadek Indah Adisari Kertiyasa; Tjokorda Gde Raka Sukawati (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This research is motivated by the increasingly fierce competition in the photography services industry, so business actors need to understand the factors that can increase consumer purchase intention. In addition, the results of previous studies regarding the influence of advertising appeal on purchase intention still show different results, so further research is needed by adding brand knowledge as a mediating variable. This study aims to examine the role of brand knowledge as a variable that mediates the influence of advertising appeal on purchase intention. The research was conducted on potential consumers of Darma Project photography services in Denpasar City with a quantitative approach using the associative method, and sample determination through a non-probability technique with a purposive sampling method, resulting in 100 respondents as the research sample. Data collection was carried out through a survey with a questionnaire instrument distributed offline and online. The theories used in this study are the Theory of Consumer Behavior and the Hierarchy of Effect Model. The data analysis technique applied is path analysis with the help of SPSS software. The implications of this research emphasize the importance of Darma Project to improve the quality and creativity of advertising to build brand knowledge through the delivery of interesting and informative information.